Canopy insect communities are shaped by the genes and phenotypes of their aspen hosts - Clay J. Morrow; Jennifer Lind-Riehl; Christopher T. Cole; Kennedy Rubert-Nason; Cécile Ané; Richard L. Lindroth (PLoS ONE, 2025)
1. Community genetics research aims to identify genetic and phenotypic mechanisms that shape communities as extended phenotypes. To date, most progress has been made identifying variation in herbivore communities associated with intraspecific variation in plants, with little focus on identifying specific genes or traits responsible for that variation. Here, we identify how extended phenotype variation of a foundation tree species, Populus tremuloides, arises from trait variation among individuals and specific genes. 2. We quantified heritability for 13 tree traits -- including phenology, defense chemistry, reproduction, and morphology -- and for 18 associated insect species (640,557 individuals). We performed genomic association analyses to identify genetic links to heritable traits and insects. 3. We found that both tree traits and communities of insect herbivores were highly heritable, and that structure and diversity of insect communities responded to heritable aspen traits. The most heritable insects were leaf-modifying specialist herbivores. We identified 73 genes associated with tree traits linked to insect communities and an additional 15 genes associated directly with insect community composition. 4. By linking intraspecific variation to community composition and structure through probable genomic mechanisms, this work demonstrates the salience of the genes-to-ecosystems paradigm in plant-insect systems.